Correlation between Pregnancy Outcome and Placental Pathology in COVID-19 Pregnant Women - Sara A. Al-Rawaf; Enas T. Mousa; Noora M. Kareem (Hindawi Limited, 2022)
Background. Vertical transmission of several viruses during pregnancy has been shown to cause adverse fetal outcomes. The question about the possibility of a similar outcome in association with SARS-CoV-2 has been raised in recently published articles. Indeed, the rate of transmission through the placenta to the fetus reported in women with COVID-19 has been shown to form a minority. The aim of this study was to explore the possible histopathological changes in the placenta of pregnant women with COVID-19 after delivery and those changes in the umbilical cord. Methods. A case-control study including a total of 50 full-term pregnant women with COVID-19 and 60 control pregnant females. Histopathological evaluation of placental tissues and umbilical cords were reported. Results. The main findings in the umbilical cord were increased thickness of vessels, thrombus formation, endothelins, and narrow lumen; except for the increased thickness of blood vessels, these findings were more frequently seen in women with COVID-19, in comparison with control women in a significant manner (p<0.05). Increased thickness of blood vessels was more significantly observed in the control group compared to the COVID-19 group (p<0.01). Findings of the placenta included avascular villi, fibrin, thrombosis, and meconium macrophage in various combinations. Except for fibrin as the sole findings, all other findings including combinations were more frequently encountered in the study group in comparison to the control group (p<0.05). Conclusion. Pregnant women with COVID-19 have significant pathological alterations in the placenta and umbilical cord. These findings reflect the capability of SARS-CoV-2 in causing immunological reactions to the placenta, either directly or indirectly, and these pathologies may be linked to the higher rate of adverse neonatal outcomes and maternal admission to the intensive care unit.